Grip to Health: Unlocking the Clinical Potential of Isometric Hand Grip Strength - A Narrative Review - Ruchi Kothari; Marina P. Johny; Dhruv Mistry; M Irfana; S Yogesh; Sai Shanmukh Vemparala (Journal of Pharmacy and Bioallied Sciences)
Isometric hand grip strength (HGS) has emerged as a simple yet powerful biomarker of overall health and functional status, particularly in aging populations. This narrative review aims to explore the clinical significance of HGS, its association with various health outcomes, and its potential as a predictive tool for morbidity and mortality. The review synthesizes evidence from diverse studies to highlight the role of HGS in assessing muscle function, cardiovascular health, and overall vitality. It discusses the utility of HGS in clinical practice, including its application in screening for frailty, predicting surgical outcomes, and monitoring chronic disease progression. Furthermore, the review addresses the limitations and challenges in standardizing HGS measurements and the need for further research to fully realize its potential in healthcare settings.